Development of Android Application Learning Media "Ruang Trigonometri" for Semester I Students of Mathematics - Putu Suarniti Noviantari (EduMa: Mathematics education learning and teaching, 2020)
This study aims to (1) produce learning media based on android learning (2) to know the level of feasibility of learning media according to material experts, media experts, and users, (3) to know the effectiveness of learning media to improve the learning outcomes of Senior high school students. This development study follows the steps developed by Alessi and Trollip, consisting of three stages: planning, designing, and development. Initial product validated by media expert and material expert then revised. The next stage is a small group beta test carried out to ten prospective users and tested on 5 users. Furthermore, test against 20 students. The results showed that (1) android-based mobile learning products packaged in android package format (apk) using app geyser software. (2) mobile learning product is considered feasible as a learning media based on the assessment of media experts 3,9 and material experts 4.2 with the category of very good. (3) the effectiveness of the product is evidenced by the increase of learning outcomes to reach the average score of pretest score 65 and post-test of 80Â Â